Implementasi Kebijakan Peraturan Bupati Gunungkidul No. 33 Tahun 2022 tentang Pengarusutamaan Gender dalam Pembangunan Daerah - Hapu Ndamayilu, Wilfridus; Koja, Marlince Tara; Lani Daghu, Daniel; Mangutu Ndamu Namu, Antonius (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
The Indonesian government affirms its commitment to gender equality, providing equal opportunities for women and men in national development, with the main aim of protecting the Indonesian nation and improving general welfare. Gunungkidul Regency, DIY, is facing serious cases of violence, especially sexual violence against minors. The government not only formulates policies, but also takes concrete steps in responding to these cases. Yogyakarta has a high risk of sexual violence, and regional regulations are an instrument for implementing gender equality in the public and private sectors. In the context of public policy, stakeholder involvement is considered important. Stakeholder analysis aims to identify the parties involved in implementing Gunungkidul Regent Regulation Number 33 of 2022. Qualitative research using the Institutional Analysis and Development (IAD) method concludes that the roles of stakeholders can be grouped into four categories. DPRD as contestants, Regional Government, Bappeda, and Police as players, society as subjects with high interests but limited power, and NGOs as supporting groups through campaigns. Stakeholder synergy is considered key to the success of policies to overcome gender gaps in Gunungkidul, ensuring the active participation of all parties to achieve the goals of gender equality and combat violence.